Pregnancy with lupus nephritis: a case report - Mishra, Vineet; Goel, Sugandha; Aggarwal, Himani; Choudhary, Sumesh (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Systemic lupus erythematosus (SLE) is an autoimmune connective tissue disorder that commonly affects women of childbearing age. Lupus nephritis in pregnancy increases risk of maternal and fetal morbidity and mortality. Active disease during pregnancy and disease flares can lead to poor outcome. Higher rates of fetal loss, preterm birth, intra-uterine growth restriction (IUGR), and neonatal lupus syndromes, gestational diabetes, osteoporosis, avascular necrosis, hypertension, preeclampsia, ecclampsia, stroke, HELLP syndrome, and maternal death are major issues. There is difficulty in recognizing disease flare because of normal physiological changes during pregnancy. Preeclampsia mimics disease symptoms of lupus nephritis and presents confusion in diagnosis. Management option is limited to few safer drugs. Lupus nephritis with antiphospholipid antibodies presents with refractory fetal loss and complete heart block associated with anti-Ro antibodies. A multidisciplinary approach, with close medical, obstetric and neonatal monitoring, is essential for optimal outcomes. Our aim is to report a case of primigravida 37 years old with controlled lupus nephritis.